Threats of bioterrorism in public health, Epidemiological clue, Detection and Safety pre-cautions for outbreaks - Shahzeb Khan; Iqra Rafi que (Open Journal of Bacteriology - Peertechz Publications, 2019)
Bioterrorism is release of biological agents such bacteria, viruses and toxin in peoples to reduce their population by causing illness which is leads to death. These bio-wars are continue panic threat in public health which is ignored and denier.